The determinants of non-performing loans : an econometric case study of Guyana - Khemraj, Tarron (UWI St. AugustineTT, 2009)
Attempts to ascertain the determinants of non-performing loans in the Guyanese banking sector using a panel dataset and a fixed effect model similar to Jimenez and Saurina (2005).